1996
DOI: 10.1002/(sici)1096-8644(199608)100:4<473::aid-ajpa3>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Physical growth of children under five years of age in Nchelenge, Zambia: Results from a district survey

Abstract: This study focuses on the physical growth of children aged 0-60 months in Nchelenge District, northeast Zambia. By means of a two-stage clustered and random sampling method, 193 households were selected. Weight, height, and mid-upper-arm circumference (MUAC) of children 0-60 months were measured. Underweight, stunting, and wasting were defined as weight for age, height for age, and weight for height (W/H), respectively, < or = 2 z scores below the median of the National Center for Health Statistics (NCHS) refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Data from another district in the same province, show similar rates of underweight and wasting (Gernaat, Dechering and Voorhoeve, 1996). However, in that study the prevalence of stunting in children below two years of age was surprisingly high in comparison with our study and showed an already high prevalence of stunting of 52% in the young age group of zero to six months.…”
Section: Discussionmentioning
confidence: 99%
“…Data from another district in the same province, show similar rates of underweight and wasting (Gernaat, Dechering and Voorhoeve, 1996). However, in that study the prevalence of stunting in children below two years of age was surprisingly high in comparison with our study and showed an already high prevalence of stunting of 52% in the young age group of zero to six months.…”
Section: Discussionmentioning
confidence: 99%